Made in Africa: How to make local agricultural machinery manufacturing thrive - Daum, Thomas; Adegbola, Ygué Patrice; Kamau, Geoffrey; Kergna, Alpha Oumar; Daudu, Christogonus; Adebowale, Wahab Akeem; Adegbola, Carine; Bett, Charles; Mulinge, Wellington; Zossou, Roch Cedrique; Nientao, Abdoulaye; Kirui, Oliver K.; et al. (Wiley, 2024)
Manufacturing has the potential to drive economic growth, job creation and poverty reduction, but African manufacturers face challenges in competing with global markets. Agricultural machinery manufacturing may be one niche where African manufacturers can succeed. This paper examines the challenges and opportunities facing local agricultural manufacturers in Africa based on a survey of 386 manufacturers in four countries and qualitative methods. Results show that small, dedicated entrepreneurs have created vibrant local machinery markets. These manufacturers have several comparative advantages, in particular, the ability to develop machinery adapted to local agroecological conditions but face challenges related to financing, human resources, utilities, raw materials, production equipment and the regulatory environment. The paper offers recommendations on how to support local manufacturers to make “Made in Africa” the first choice for African farmers and agro-food processors.